PENGARUH PENGGUNAAN TPS TERHADAP HASIL BELAJAR IPS KELAS V SDN 18 SUNGAI AMBAWANG - Lidya, Natalia; Marli, Suhardi; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to fird of out the influence of using TPS toward the outcome of IPS learning on class V SDN 18 Sungai Ambawang Kubu Raya. The method used is experimental study. With pre experimental design,with kind of experimental one grup pretest-posttest design. The technique of data collecting used is test in from of multiple choice which consist of 50 items.The result of the research is the average score of pretest 61,21, while the averagescore of post-test 74,54, t-test price tcount compared ttable with dk= 24-1=23 and the significance level (Î±) 0,05 the price of ttable=2,068.Tcount â‰¥ ttable or 7,029â‰¥ 2,068 means significant, it conclude that Ho is rejected, whereas Ha is accepted.It can be conclude that there is an influence ofÂ using TPS type of cooperative model toward the outcome of IPS learning on class V SDN 18 Sungai Ambawang Kubu Raya, that is about 0,77 with the medium category.Keywords:Influence, Learning Outcomes, Think Pair Share